Climate Change, COVID-19, and Flood disasters in Pakistan - Muhammad, Ameer; Noor, Saba (Journal of the Pakistan Medical Association, 2023)
In the aftermath of recent floods, Pakistan has been confronting several challenges such as infrastructural damages and economic decline. Despite its efforts to prepare for potential pandemics like COVID-19, limited healthcare resources, insufficient funding for research and development, and inadequate public awareness are some of the obstacles that hinder its full preparedness.1 The recent floods have further aggravated Pakistan’s struggle to contain COVID-19 by disrupting healthcare services and vaccine distribution.2 Additionally, climate change is affecting maternal and child health in the country, with extreme weather events, such as floods and droughts, causing a decrease in access to essential resources like food and water, and an increase in disease exposure, which ultimately impacts the overall wellbeing of the population.3 Such as malnutrition and the spread of waterborne diseases have a direct impact on the health of pregnant women and children, increasing the risk of complications during pregnancy and delivery and increasing the risk of illness and premature birth, low birth weight, and other health problems in new-borns or even death in early childhood.4,5 Addressing the impact of climate change, COVID-19, and floods on the affected areas in Pakistan requires a multi-faceted approach that involves multiple sectors, including the government, healthcare, and the private sector. Some of the key solutions include: Improving access to healthcare: Increasing the number of healthcare facilities and ensuring that they are equipped with the necessary resources, including personal protective equipment, to respond to the COVID-19 pandemic and other health emergencies. Improving access to clean water and sanitation: Providing clean water and sanitation facilities in affected areas to reduce the risk of waterborne diseases, particularly in the aftermath of floods. Strengthening disaster preparedness and response: Implementing effective disaster preparedness and response plans to ensure that communities are prepared for and can quickly respond to extreme weather events and other disasters. Increasing funding for research and development: Supporting research and development activities to find solutions to the challenges posed by climate change, COVID-19, and other health emergencies. Improving public awareness: Increasing public awareness about the importance of preventative measures, such as vaccination, hand hygiene, and healthy behaviours, to prevent the spread of COVID-19 and other diseases. Promoting sustainable development: Encouraging sustainable development practices, such as the use of renewable energy sources and conservation of natural resources, to reduce the impact of climate change on the environment and health.